The Oldenburg observation sheet for table tennis technique (O3T) as a tool for talent identification and development: a reliability, validity and feasibility study - Koopmann, T.; Faber, I.; Büsch, D.; Schorer, J. (International Journal of Racket Sports Science, 2022)
Background: The assessment of technical skills as part of a multidimensional approach for talent identification and development in table tennis appears promising. The O3T was developed to assess young table tennis players` technical skills in a highly representative match situation. In this study, two expert coaches (highest coaching license, 25+ years of professional experience) used the O3T to assess the technical skills of 24 young Dutch table tennis players (9 girls, 15 boys; <12 years) based on video recordings. Results: Results for variables `technical quality`, `serve quantity` and `stroke quantity` were analyzed to assess the O3T`s reliability (both inter- and intra-rater), construct validity and feasibility. Bland-Altman-plots and ICCs showed sufficient general reliability with acceptable measurement errors. Variable `technical quality` showed a moderate relationship (r = .44) with overall table tennis performance at T0 in combination with an increasing trend over time, this way indicating high validity. Finally, the O3T proved to be highly feasible with some possibility to improve based on a feasibility questionnaire. Conclusions: Overall, this study presents good prospects for the O3T`s measurements properties. In future, the O3T should be used by coaches in various (talent) contexts to further improve its design and to show its added value for talent activities. Furthermore, this approach could be transferred to other performance aspects and sports.